WIE Fight: Women in Robotics Team - Silva, Patrícia S.; Albrecht, Luiza M. A.; Leal, Luize G. C. S.; Balue, Eduarda A.; Canella, André L.C.; Alves, Laís A.; Pinto, Milena F. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
The underrepresentation of women in robotics re-flects broader gender disparities in STEM fields, notably in engineering courses. This complex issue stems from various factors and often requires targeted initiatives to address it. Therefore, this paper outlines the outcomes of an action research project named WIE FIGHT, which aims to foster women's interest in robotics within STEM education by forming an all-female team to develop a competitive combat robot. This publication presents an overview of the project's evolution, from participant training to developing the first robot prototype. The survey results reveal that participants had a positive influence, as evidenced by improved knowledge and enthusiasm for engaging with robots in both learning and practical applications.